Mechanistic Aspects of [3+2] Cycloaddition Reaction of Trifluoroacetonitrile with Diarylnitrilimines in Light of Molecular Electron Density Theory Quantum Chemical Study - Agnieszka Łapczuk; Mar Ríos-Gutiérrez (Molecules)
In this study, we investigated the [3+2] cycloaddition reaction of CF3CN (TFAN) with nitrilimine (NI) to produce 1,2,4-triazole and compared the resulting isomers. We determined the preferred reaction pathway by examining the electrophilic and nucleophilic properties of the reaction substrates, performing thermodynamic calculations for the individual pathways, and comparing them with the experimental results.